BIMBINGAN DAN DUKUNGAN PENERAPAN PENGGUNA TEKNOLOGI PADA PERUSAHAAN KONSULTAN TI - Lee, Francka Sakti; Andry, Johanes Fernandes; Terry, Johanes; Liawen, Callista Chrestella; Theresia, Jennifer (Universitas Bunda Mulia, 2026)
Brainware refers to individuals directly involved in operating, organizing, and managing computer systems, which are a crucial component of an information system. Standard Operating Procedures (SOPs) are documents that explain responsibilities and how each task is performed to support specific company goals. An IT Security Policy plays a role in implementing the necessary measures to minimize and anticipate potential threats to a company's confidential information. Enhancing consumer data security is not only an individual's responsibility but also the organization's in building consumer trust and complying with regulations. The variety and variability of risks are concerns for all companies. The increasing use of the internet has led to a rise in data breaches caused by more cyberattacks. Companies today face threats that can jeopardize their reputation, highlighting the role of brainware in addressing these threats. Therefore, awareness and knowledge of each individual are necessary to motivate the implementation of steps to overcome these threats. An IT Security Policy can be implemented with the expectation that all parties involved know their specific responsibilities within a company. This is necessary to maintain the technological ecosystem within a corporate organization.